2013
DOI: 10.1016/j.diii.2013.06.013
|View full text |Cite
|
Sign up to set email alerts
|

The lower cranial nerves: IX, X, XI, XII

Abstract: The lower cranial nerves innervate the pharynx and larynx by the glossopharyngeal (CN IX) and vagus (CN X) (mixed) nerves, and provide motor innervation of the muscles of the neck by the accessory nerve (CN XI) and the tongue by the hypoglossal nerve (CN XII). The symptomatology provoked by an anomaly is often discrete and rarely in the forefront. As with all cranial nerves, the context and clinical examinations, in case of suspicion of impairment of the lower cranial nerves, are determinant in guiding the ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0
6

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 12 publications
2
39
0
6
Order By: Relevance
“…BCL11A is a known interactor of COUP‐TF1 and COUP‐TF1 knockout in mice results in malformations of the glossopharyngeal ganglion (Avram et al, 2000, 2002; Qiu et al, 1997). In humans the glossopharyngeal nerve and ganglion are responsible for motor (stylopharyngeal) and sensory innervation of the upper pharynx, and parasympathetic innervation of the parotid gland (Sarrazin, Toulgoat, & Benoudiba, 2013). Hence, the hypothesis of BCL11A mediating a dysfunction of the glossopharyngeal nerve could, at least partially, explain the oro‐praxic and phonological deficits and excessive drooling present in the described patients.…”
Section: Discussionmentioning
confidence: 99%
“…BCL11A is a known interactor of COUP‐TF1 and COUP‐TF1 knockout in mice results in malformations of the glossopharyngeal ganglion (Avram et al, 2000, 2002; Qiu et al, 1997). In humans the glossopharyngeal nerve and ganglion are responsible for motor (stylopharyngeal) and sensory innervation of the upper pharynx, and parasympathetic innervation of the parotid gland (Sarrazin, Toulgoat, & Benoudiba, 2013). Hence, the hypothesis of BCL11A mediating a dysfunction of the glossopharyngeal nerve could, at least partially, explain the oro‐praxic and phonological deficits and excessive drooling present in the described patients.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with oropharyngeal cancer (OPC) receive local treatments, radiotherapy (RT), and/or surgery, to this functionally critical region that can cause chronic dysphagia with adverse impact on swallowing-related quality of life (QOL). [1][2][3][4][5][6] Dysphagia is one of the most impactful and prevalent functional toxicities reported in approximately 30%-50% of survivors. [7][8][9][10] Prior analysis of this OPC survivorship found that, among 22 symptoms queried, the severity of dysphagia symptoms most strongly associated with decisional regret about cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Otros autores estiman que emerge entre la oliva inferior y el pedúnculo cerebeloso inferior (13,14); incluso se cita que emerge del surco lateral de la médula, caudal al nervio facial (15). También se señala que tiene su origen en la parte superior del surco colateral posterior (16,17), o que se ubica en el surco retro-olivar (5,6,18,19) o surco post-olivar (20). Asimismo, se afirma, sin dar mayores detalles, que emerge detrás de la oliva (21).…”
Section: Introductionunclassified
“…Nervio vago: está conformado por 10 a 15 raíces procedentes de la medula oblonga, por detrás de la oliva (21,22) o lateral a ella (14,23,24) e incluso en el tercio superior de su cara lateral (10,11). Chatain & Bustamante (12) le dan una ubicación más específica a este nervio al señalar que emerge con 16 filetes radiculares del surco dorsolateral de la médula oblongada, por debajo del nervio glosofaríngeo, mientras que otros autores describen que las fibras del vago emergen del surco retro-olivar (5,6,18,19) o fisura post-olivar (7,9). También se señala que la emergencia de este ocurre por el surco colateral del bulbo (16,17), entre los nervios glosofaríngeo y accesorio (16); Pansky (15) lo ubica en el surco lateral de la médula y Escobar & Pimienta (25) indican que se origina de la médula oblongada, sin especificar el sitio exacto.…”
Section: Introductionunclassified
See 1 more Smart Citation